Рrospects for the use of "dry" carbon dioxide baths in patients with chronic viral hepatitis c with concomitant non-alcoholic fatty liver disease (literature review and own research) - Anna Izha (Kazimierz Wielki University, 2020)
The paper analyzes modern views on the etiology, epidemiology, pathogenesis, methods of treating patients with chronic viral hepatitis C with concomitant non-alcoholic fatty liver disease (NAFLD), discusses the possibility of using "dry" carbon dioxide baths (DCDB) in this category of patients. Our research was conducted to study the effectiveness of the integrated use of antiviral therapy (AVT) and DCDB procedures in patients with chronic hepatitis C with concomitant NAFLD. The authors of the study were the first to suggest using of DCDB in this category of patients. Based on the results obtained, for the first time, ideas about the specificity of the DCDBʹs effect on the clinical course of the underlying and concomitant diseases, on the functional state of the liver, the dynamics of lipid metabolism, and ultrasonographic parameters of the liver were detailed. It is concluded that DCDB can be successfully used in the complex treatment of patients with chronic hepatitis C with concomitant NAFLD.